Building Knowledge in the Virtual World – Influence of Real Life Relationships - Loureiro, Ana (2022)
his paper intends to present a preliminary PhD research that is being developed by the authors, with the intention to determine how to improve teaching and learning situations, at the university level, based on experiences in immersive virtual worlds. The authors have realized that, nowadays, courses don’t fulfill our students’ needs. They belong to a networked and multitasking generation, and what they get from today’s teaching strategy does not, in many situations, fulfill students’ needs and perspectives. They need to gather competences in order to become motivated citizens, communicative and knowledge builders. It is our belief that we can take advantage from the immersive virtual worlds’ resources to overcome this situation and therefore to transfer it to real life. In order to achieve this we need, at the first instance, to understand how social interactions occur in these environments (in particular at Second Life®), how they grow and how they are developed. What we present here is a preliminary sample of our intended research.